The AGXX® Antimicrobial Coating Causes a Thiol-Specific Oxidative Stress Response and Protein S-bacillithiolation in Staphylococcus aureus - Loi, Vu Van; Busche, Tobias; Preuß, Thalia; Kalinowski, Jörn; Bernhardt, Jörg; Antelmann, Haike (Frontiers in Microbiology, 2018)
Multidrug-resistant pathogens, such as methicillin-resistant Staphylococcus aureus (MRSA) pose an increasing health burden and demand alternative antimicrobials to treat bacterial infections. The surface coating AGXX® is a novel broad-spectrum antimicrobial composed of two transition metals, silver and ruthenium that can be electroplated on various surfaces, such as medical devices and implants. AGXX® has been shown to kill nosocomial and waterborne pathogens by production of reactive oxygen species (ROS), but the effect of AGXX® on the bacterial redox balance has not been demonstrated. Since treatment options for MRSA infections are limited, ROS-producing agents are attractive alternatives to combat multi-resistant strains. In this work, we used RNA-seq transcriptomics, redox biosensor measurements and phenotype analyses to study the mode of action of AGXX® microparticles in S. aureus USA300. Using growth and survival assays, the growth-inhibitory amount of AGXX® microparticles was determined as 5 µg/ml. In the RNA-seq transcriptome, AGXX® caused a strong thiol-specific oxidative stress response and protein damage as revealed by the induction of the PerR, HypR, QsrR, MhqR, CstR, CtsR and HrcA regulons. The derepression of the Fur, Zur and CsoR regulons indicates that AGXX® also interferes with the metal ion homeostasis inducing Fe2+- and Zn2+-starvation responses as well as export systems for toxic Ag+ ions. The induction of the SigB and GraRS regulons reveals also cell wall and general stress responses. AGXX® stress was further shown to cause protein S-bacillithiolation, protein aggregation and an oxidative shift in the bacillithiol (BSH) redox potential. In phenotype assays, BSH and the HypR-controlled disulfide reductase MerA were required for protection against ROS produced under AGXX® stress in S. aureus. Altogether, our study revealed a strong thiol-reactive mode of action of AGXX® in S. aureus USA300 resulting in an increased BSH redox potential and protein S-bacillithiolation.